134 Peripartum supplementation of vitamins A, D, and E improves measures of vitamins A, D and E in beef cows and their calves. (7th December 2018) - Canal, L; Maciel, J; Fontes, P; Sanford, C; Oosthuizen, N; Blakely, L; Pozadas, M; da Silva, R; Litta, G; Engstrom, M; DiLorenzo, N; Lamb, G; et al.
Abstract: The objective of the experiment was to determine the effects of different supplemental sources of vitamins A, D, and E on fat-soluble vitamin status of beef cows and subsequent calves when provided during the peripartum period. Fifty six cross-bred beef cows housed at the North Florida Research and Education Center were stratified by age and then randomly assigned to 1 of 3 treatments: CTRL (n = 19): mineral supplement containing 9.5 mg (28, 000 IU) of retinyl-acetate and 0.23 mg (9, 200 IU) of vitamin D3 daily; VIT1 (n = 19): supplement with additional 34 mg (100, 000 IU) of retinyl-acetate, 1 mg (40, 000 IU) vitamin D3, and 500 mg (500 IU) a-tocopherol-acetate; or VIT2 (n = 18): supplement with additional 250 mg b-carotene, 1 mg 25-hydroxyvitamin D3, and 1, 000 mg a-tocopherol-acetate. Cows were fed bermudagrass ( Cynodon dactylon ) hay ad libitum and treatments were provided individually from 250 d of gestation to 60 d postpartum as top-dress to 0.91 kg/d of cottonseed meal. Blood samples were collected from all cows on d 250 and 271 of gestation as well as 1, 7, 30 and 60 d postpartum. Blood samples were collected from calves at 1, 7, and 30 d of age. Data were analyzed for the effects of treatment, day, and treatment × day interactions. b-carotene and 25-hydroxyvitamin D serum concentrations were greater ( P < 0.01) in the VIT2 treatment. In addition, colostrum concentration of retinol ( P = 0.06), b-carotene ( P = 0.08), and a-tocopherol ( P = 0.04) were greater in cows in the VIT2 treatment. Furthermore, VIT1 and VIT2 treatments increased ( P < 0.01) serum concentrations of b-carotene, 25-hydroxyvitamin D and a-tocopherol in calves. In conclusion, supplementation of b-carotene and vitamins D and E during late gestation and early lactation improves fat-soluble vitamin status of beef calves.